Making History In Borneo: Ong Sum Ping And His Others During The Late Yuan And Early Ming Dynasties - Kurz, Johannes L. (Penerbit Universiti Sains Malaysia (USM Press), 2018)
The Genealogy of the Sultans of Brunei (Silsilah Raja-raja Brunei) introduces an alleged Chinese ancestor whose name has been transcribed as Ong Sum Ping. Ong is said to have been related to the imperial family of China, to have ruled over Sabah in northern Borneo, and having provided his sister as spouse to one of the early sultans of Brunei. The current paper examines Ong Sum Ping and his various appearances under diﬀerent names in especially Chinese texts from the twentieth century. These texts emphasise early Chinese inﬂuence on northern Borneo. Sometimes Ong Sum Ping is linked to Manarejiana, a Boni chieftain, who visited Nanjing, the capital of the Ming empire in 1408 to pay tribute and his respects to the Yongle emperor (r. 1402–1424). Through the association of the chieftain with the Ming empire, some writers suggest that Ong Sum Ping may have been an admiral of Zheng He’s ﬂeet who came to Brunei and stayed there. At the core of the paper is an examination of modern assumptions about: (1) the identity of Ong Sum Ping; (2) the existence of a Chinese province in northern Borneo; and (3) the likelihood of an appearance of the Treasure Fleet of Zheng He in Brunei in the early ffteenth century. I argue that with the extant Chinese textual sources none of these claims can be verifed, and that therefore they are reﬂecting local oral traditions.